Transpulmonary pressures in obese and non-obese COVID-19 ARDS - Mezidi, Mehdi (Ann Intensive Care, 2020)
BACKGROUND: Data on respiratory mechanics of COVID-19 ARDS patients are scarce. Respiratory mechanics and response to positive expiratory pressure (PEEP) may be different in obese and non-obese patients. METHODS: We investigated esophageal pressure allowing determination of transpulmonary pressures (PL ) and elastances (EL) during a decremental PEEP trial from 20 to 6 cm H(2)O in a cohort of COVID-19 ARDS patients. RESULTS: Fifteen patients were investigated, 8 obese and 7 non-obese patients. PEEP ≥ 16 cm H(2)O for obese patients and PEEP ≥10 cm H(2)O for non-obese patients were necessary to obtain positive expiratory P(L). Change of PEEP did not alter significantly ΔP(L) or elastances in obese patients. However, in non-obese patients lung EL  and ΔP(L) increased significantly with PEEP increase. Chest wall EL was not affected by PEEP variations in both groups.